Oklahoma in words and pictures - Fradin, Dennis B.; Wahl, Richard, 1939-; Meents, Len W. (Chicago : Childrens Press, 1981)
A brief introduction to the history, geography, industries, cities, tourist attractions, and famous citizens of Oklahoma, the state that has more Indians than any other state.
School Library Journal
5.5
3-6
Keywords: Oklahoma -- Juvenile literature; Oklahoma; Oklahoma